The The Implementation of Scientific Approach in Teaching Speaking with Appropriate Lesson Plan Based on 2013 Curriculum - Sodik, Fajar; Faridi, Abdurrachman; Saleh, Mursid (English Education Journal, 2020)
This study focused on the implementation of scientific approach in teaching speaking with appropriate lesson plan. The steps consist in observing, questioning, associating, experimenting and communicating. This study also focused on the appropriateness of lesson plan viewed from 2013 curriculum guideline. This study used case study in qualitative descriptive. The sample in this study was three English teachers at SMP Negeri 40 Semarang. The result shows that English teachers at SMP Negeri 40 were implementing scientific approach based on 2013. The implementation was in five main steps. They were observing, questioning, associating, experimenting and communicating. All the steps had been implemented well based on 2013 curriculum. There were some problems in implementing scientific approach. The problems in implementing scientific approach in teaching speaking were in communicating step and the difficulties in time management, confidence of the students and also pronunciation. Related to the appropriateness of the lesson plan, all the principles and criteria had been fulfilled except the attention on the students’ differences and developing the culture in reading and writing. The finding can be used by as a reference in implementing scientific approach.